Intention to consume cultured meatballs among the youths in Malaysia, a behavioural study - Chai, Li Xin (2023)
The Myogenesis process develops culture meat from animal cells that is edible and tastes like animal meat. However, the product is yet to be marketed in Malaysia as the government or product suppliers are uncertain of the demand in the local market although the product is marketed in other countries. In filling the knowledge gap, this project examines whether a potential market: Malaysian youth has the intention to consume cultured meatballs. The youth is targeted because young people are more willing to try newly developed products compared to other younger and older aged group population. In order to provide information to policy-makers in Malaysia public and private agencies, this project examined behavioural variables influence on the youths’ cultured meatball consumption intention. In identifying the potential behavioural variables, a preliminary study was carried out. The result shows the following behavioural variables - product awareness, attitude, subjective norms (SN) and perceived behavioural control (PBC) – are playing important roles and guide current research to modify the theory of planned behaviour (TPB) model by including an additional variable: product awareness as a predictor construct which is less tested in literature related to food consumption. As the TPB model and product awareness variables have been tested in literature, this project adapts the past studies items to suit the current study context. The item statements then were checked and refined after getting feedback from pre-test expert and pilot study participants. In the main study, 384 respondents resided in Malaysia were engaged using snowball sampling method. In testing current hypotheses, multiple regression is used after the prior statistical tests result support the validity and reliability of data collected from the main study. The regression result shows that all hypotheses are supported. Tactical strategies are recommended based on the examined items of each variable. The project limitations are discussed and recommendations are provided for future researchers’ reference.